Black Start and Voltage Establishment Strategy for PMSG-Based Wind Turbine - Ji, Xiaotong; Liu, Dan; Hu, Pan; Cao, Kan; Jiang, Kezheng; Huang, Guohang; Huang, Sheng (Frontiers in Energy Research, 2022)
During the black start, backup ac power sources like diesel generators can offer line-side voltage reference for wind turbine and keep line-side converter of wind turbine work properly so that the dc-link capacitor voltage within converter can be established without overcharge. This paper proposes a black start control strategy and line-side voltage establishment method for PMSG based wind turbines with no ac power source. Unlike the traditional control strategy of full power grid-connected converters, the dc-link voltage within back-to-back full power converters of wind turbines can be controlled by generator-side converters, and the line-side voltage can be established by line-side converters with the help of fixed loads. The mechanical power can be balanced by pitch angle control, and the power unbalance between mechanical power and electrical power will be reflected in rotor speed of PMSG. By this method, a single wind turbine can establish the line-side voltage with no extra backup ac power source, offering voltage reference for the other wind turbines during the black start of a wind power plant.